Impediments of Green Finance Adoption System: Linking Economy and Environment - Kanwal Iqbal Khan; Mário Nuno Mata; Adeel Nasir; Rui Miguel Dantas; Anabela Batista Correia; Mahr Umar Saghir; José Moleiro Martins (Ital Publication, 2022)
Environmental deregulation has become a severe concern for public health around the world. Increased pollution and ecological degradation have diverted attention towards adopting green practices, which can be possible if the sustainable green finance system is implemented in its true spirit. But previous studies reported certain factors affecting its implementation process, particularly in developing countries. This study aims to identify and quantify the barriers to adopting a green finance system. First, it identified twenty barriers through an extensive literature review and semi-structured interviews with experts in the fields of financial management, economics, and environmental sciences. Later, eighteen factors were finalized by the consensus of panel experts, which was further used to analyze their interrelationship through Interpretive Structural Modelling (ISM). Using MICMAC analysis, these barriers were categorized based on their diving-dependence powers. Finally, the conceptual ISM model is developed that provides a clear picture of the impediments to the green finance adoption system and their flow relationship among the identified barriers at different levels. The findings suggest that global level factors: lack of pressure from international organizations and unavailability of globally acceptable green criteria are critical to the prevalence of other factors that indicate its centrality to effectively implementing the green finance system. The developed model helps in designing, implementing, and promoting eco-friendly projects. It is also recommended that an appropriate framework is required to be developed at global, country, organizational, and individual levels to deal with the barriers of the green finance adoption system. Doi: 10.28991/ESJ-2022-06-02-02 Full Text: PDF